Guilt in voting and public good games - Dominik Rothenhäusler; Nikolaus Schweizer; Nora Szech (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2016)
This paper analyzes how moral costs affect individual support of morally difficult group decisions. We study a threshold public good game with moral costs. Motivated by recent empirical findings, we assume that these costs are heterogeneous and consist of three parts. The first one is a standard cost term. The second, shared guilt, decreases in the number of supporters. The third hinges on the notion of being pivotal. We analyze equilibrium predictions, isolate the causal effects of guilt sharing, and compare results to standard utilitarian and non-consequentialist approaches. As interventions, we study information release, feedback, and fostering individual moral standards.
urn:nbn:de:swb:90-685039
Keywords: D02; D03; D23; D63; D82; 330; Moral Decision Making; Committee Decisions; Diffusion of Responsibility; Shared Guilt; Being Pivotal; Division of Labor; Institutions and Morals